Positioning the Flipped Classroom Process for Adult Learning (Unilorin Journal of Lifelong Education, 2025)
The flipped classroom methodology is an evolving concept that has become enhanced by modern technology. The approach proceeds by delivering instruction to learners through a recorded video, while turning formal class time into a time for some learner-centered knowledge discovery activity. Thus, the flipped classroom is a learner-centered approach to learning. However, there have been a tendency in the literature to cast the flipped classroom approach as the ideal approach for engaging adult learners. This paper argues that while the flipped classroom methodology is a learner-centered knowledge discovery approach to learning, the approach does not necessarily satisfy all the desiderata of an adult learning theory. Although, class flipping will allow the learner to bring their prior experience to bear on those class activity sessions, it remains the case that the facilitator is still in absolute control of the process of setting the learning agenda and the evaluation thereof, without any input from the learners. In order to leverage on the advantages of flipped classrooms with respect to adult learning, there is a need to blend the flipped classroom process with the existing principles of adult learning. This will enable the derivation of an adult learning-oriented flipped classroom process model. This paper proposes such a process model that uses the flipped mastery process and appropriately apportions responsibilities using the principles of andragogy.